Determinan Pertumbuhan Agregat Aset Perusahaan Asuransi Syariah Pasca Spin-Off: Peran Mediasi Earning After Tax - Deni Mukti Hidayat; Soeharjoto Soeharjoto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine the determinants of aggregate assets in Islamic insurance companies in Indonesia by analyzing the effects of contribution income, investment returns, and cost efficiency, as well as evaluating the mediating role of earning after tax. The study employs a quantitative approach using panel data and applies the Fixed Effect Model (FEM) along with mediation analysis. The empirical results indicate that contribution income and cost efficiency have a positive and significant effect on aggregate assets, while investment returns and earning after tax do not have a direct significant effect. The mediation analysis reveals that earning after tax only mediates the relationship between cost efficiency and aggregate assets, but does not mediate the effects of contribution income or investment returns on aggregate assets. These findings suggest that asset growth in Islamic insurance companies is primarily volume-driven and efficiency-driven rather than profit-retention driven, as commonly assumed in conventional firm growth theory. Theoretically, this study contributes to the Islamic finance literature by proposing a more contextual aggregate asset model that reflects the structural characteristics of the Islamic insurance industry. Practically, the results emphasize the importance of strengthening contribution growth and operational efficiency strategies to support sustainable asset expansion in Indonesia’s Islamic insurance sector